HUBUNGAN TINGKAT PENGETAHUAN HAND HYGIENE DENGAN KEPATUHAN PELAKSANAAN HAND HYGIENE PADA PESERTA PROGRAM PENDIDIKAN PROFESI DOKTER - Anietya Widyanita; Ekorini Listiowati (Universitas Muhamadiyah Surakarta, 2014)
Prevention and Control Program (PPI) including hospital accreditation assessment. One of the standard phase is hand hygiene. The hands of health care are often contact with the patient and his environment, thus becoming the most common transmission of HAIs. Hand hygiene can reduce HAIs if done with appropriate recommendation. This study was conducted to determine the relationship between the level of knowledge of hand hygiene and hand hygiene compliance implementation. This study was observational analytic with cross sectional approach. Subjects were participants of educational programs in the medical profession with a total sampling technique. Instrument research using questionnaires and observation sheet. Analyzed with descriptive statistics, the average level of knowledge and implementation of hand hygiene compliance in respondents is less. Analysis distribution of respondents by sex, male totaled 17 people and female totaled 14 people, distribution of respondents according to the level of knowledge, less value totaled 29 people (93.5%) and enough value totaled 2 people (6.5%), distribution of respondents according to the level of compliance, less value totaled 26 people (83.9%) and good value totaled 5 people (16.1%). Analysis using a correlation test, 0.599 correlation value, where p0.005, positively related. This study shows that there is a positive relationship between the level of knowledge of hand hygiene and hand hygiene compliance implementation. The average level of knowledge has less value. The average rate of hand hygiene compliance implementation has less value.Keywords: Knowledge level of hand hygiene-Implementation of hand hygiene compliance